The historical development and juridical issues of the common law concept of professions - Abd Rahman, Hussin Mohamed; Abd Ghadas, Zuhairah Ariff; Alias, Siti Aliza (2015)
Introduction The term ‘profession’ has no statutory definition.884 In light of the statutory lacuna, the common law has initiated an important thrust in laying down the legal concept of profession and its related ideas, where specifically the dictum and the approach of Lord Justice Scrutton in Commissioners of Inland Revenue v. Maxse885 represents a milestone in the juridical idea of profession. His Lordship’s approach has provided a seminal framework making the subsequent judicial development in this area possible. The development of judicial approach relating to the legal concept of profession may be analysed in different stages. The following stages are suggested for the present analysis.